Retinoid plus antimicrobial combination treatments for acne - Feneran A; Kaufman WS; Dabade TS; Feldman SR (Clinical, Cosmetic and Investigational Dermatology, 2011)
Ashley N Feneran1, William S Kaufman2, Tushar S Dabade1, Steven R Feldman1,3,41Department of Dermatology, Center for Dermatology Research, Wake Forest University School of Medicine, Winston-Salem, NC, USA; 2Medical College of Virginia, Richmond, VA, USA; 3Department of Pathology, Center for Dermatology Research, Wake Forest University School of Medicine, Winston-Salem, NC, USA; 4Department of Public Health Sciences, Center for Dermatology Research, Wake Forest University School of Medicine, Winston-Salem, NC, USABackground: Acne vulgaris is a chronic disease with several pathogenic factors. Multiple medications are typically used that can lead to nonadherence and treatment failure. Combination medications target multiple pathways of acne formation and may offer therapeutic benefit.Purpose: To explore the efficacy and tolerability of combination retinoid plus antimicrobial treatments in acne vulgaris.Methods: A PubMed and Google search was conducted for combination therapies of clindamycin and tretinoin, with secondary analysis of related citations and references. Similar searches were completed for the combination medications of benzoyl peroxide plus clindamycin or erythromycin, and for the combination therapy of adapalene and benzoyl peroxide.Results: Combination clindamycin phosphate and tretinoin gel was found to be more efficacious than monotherapy of either drug or its vehicle for acne, including inflammatory acne, and has a greater onset of action than either drug alone. Clindamycin phosphate and tretinoin gel was well-tolerated, and adherence to its use exceeded that of using both medications in separate formulations. Benzoyl peroxide-containing combination medications with clindamycin or erythromycin were both more effective in the treatment of acne than either drug alone. Both medications were well-tolerated, with dry skin being the most common adverse effect.Conclusions: Combination medications have superior efficacy and adherence, and have a similar tolerability profile compared with monotherapy of its components. Several studies have found antibiotic-containing combination products with a retinoid effective for acne. The use of antibiotic-containing combination medications for acne can lead to bacterial resistance. Due to this potential for bacterial resistance, benzoyl peroxide treatments are also recommended in combination with a retinoid.Keywords: erythromycin, adherence, efficacy, safety, tolerability